Hepatoprotective and antioxidant activities of Spondias mombin leaf and stem extracts against carbon tetrachloride-induced hepatotoxicity - Nwidu, Lucky Legbosi; Elmorsy, Ekramy; Yibala, Oboma I.; Carter, Wayne (Elsevier, 2018)
Objective